TGF-β in transplantation tolerance. - Regateiro, F; Howie, D; Cobbold, S; Waldmann, H (2011)
TGF-β is a cytokine required for the induction and maintenance of transplantation tolerance in animal models. TGF-β mediates anti-inflammatory effects by acting on many immune cell-types. Central for transplantation tolerance is the role for TGF-β in the induction of Foxp3 and regulatory capacity in CD4(+) T cells. Recently, however, the general anti-inflammatory role of TGF-β in CD4(+) T cell polarization was questioned by the discovery that, in the presence of inflammatory cytokines such as IL-6 or IL-1, TGF-β drives the differentiation of Th17 cells associated with transplant rejection. A better understanding of the factors determining TGF-β production and activation, Foxp3 induction and Treg stability is vital for the development of tolerogenic strategies in transplantation.